The effectiveness of physiotherapy in cervicogenic headache and concurring temporomandibular dysfunction: a case report - F. Lewis; B. Naude (AOSIS, 2010)
The aim of this case report is to describe the use of physio-therapy interventions in a patient diagnosed with cervicogenic headache(CGH) and temporomandibular dysfunction (TMD). This case study involveda 26 year old male. The subject's cervical and temporomandibular joint(TMJ) active range of movement; passive accessory movements; headacheintensity, periodicity and response to analgesics; TMJ clicking and discomfort;Numerical Pain Rating Scale (NPRS) scores, were assessed on initial assessment and on discharge 14 weeks later. The physiotherapy interventionincluded cervical and TMJ mobilisation (Maitland approach); trigger pointtherapy and massage; strengthening of the deep cervical neck flexors and scapulothoracic muscles; and posture correction. The subject improved on all outcome measures and was discharged after nine physiotherapy sessions, withfull cervical and TMJ range of movement, improved muscle strength and decreased headache intensity and frequency.This case describes a positive outcome for a patient diagnosed with cervical headaches and temporomandibular dysfunction in which physiotherapy interventions aimed at correcting joint dysfunction, myofascial pain and decreased muscle strength were used effectively.